Peningkatan Hasil Belajar Matematika Penjumlahan Melalui Menggunakan Media Konkret Pada Siswa Kelas II - Arita s; Erwin Nurdiansyah; Mulyadi; Abdul Wahid (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to improve students' mathematics learning outcomes in addition material through the use of concrete media for second-grade students at UPT SDN 124 Tedeboe. This research was Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection stages. The subjects were second-grade students of UPT SDN 124 Tedeboe. Data were collected through learning achievement tests, observations, and documentation. The results showed that the use of concrete media improved students' learning outcomes in addition material. Students became more active, enthusiastic, and better understood addition concepts through direct manipulation of real objects. Learning mastery increased from the pre-cycle to cycle I and cycle II. Therefore, concrete media effectively improved mathematics learning outcomes in addition material for second-grade students at UPT SDN 124 Tedeboe